PENDIDIKAN LINGKUNGAN HIDUP (PLH) SEBAGAI UPAYA KONSERVASI CENDERAWASIH KUNING KECIL DENGAN PARTISIPASI GENERASI MUDA DI KAMPUNG BARAWAI DISTRIK RAIMBAWI KABUPATEN KEPULAUAN YAPEN - Edoward Krisson Raunsay; Dolfina Costansah Koireowa (JURNAL PENGABDIAN PAPUA, 2019)
The aims of this activities were to transfer knowledge and give an understanding about the importance of conserving Cenderawasih Kuning Kecil (Paradisaea minor) for the youth in Barawai District, Yapen Island Regency. Lectures Focus Group Discussion and Case Study were used as methods this time. We could conclude that people from all ages range were actively participated in our community services program and as a result the eye awarded by Satyalencana and Kalpataru as a form of high dedication in conserving wild animals and their habitats.Keywords: conserving, Paradisaea minor, Barawai, Kepulauan Yapen